THE CHANGING BEHAVIOUR OF NEW ONSET IBD IN IRISH CHILDREN FROM 2010–2011. (8th June 2013) - Carey, A; O'Gorman, J; Cafferty, A; O'Driscoll, K; Hamzawi, M; Bourke, B; Broderick, A; Hussey, S
Abstract : Introduction: The rise in the incidence of paediatric inflammatory bowel disease (IBD) in Ireland from 2000 to 2010 has been recently documented. Aims/Background: The aim of this current study was to examine the phenotypic attributes of IBD among children diagnosed with new onset IBD in 2010 to 2011. Method: A retrospective review of paediatric IBD was undertaken using nationally representative data from the National Centre for Paediatric Gastroenterology, Hepatology and Nutrition (NCPGHN) in Ireland. IBD was phenotyped using the Paris classification and compared against previous Irish data from 2000 and 2008 and international figures. Data was analysed using the Statistical Package for Social Sciences (SPSS). Results: The incidence of IBD from October 2010 to October 2011 was 7.5/100, 000/year. Seventy nine children were diagnosed with IBD during the defined review period (49 boys, 32 girls, median age of diagnosis 12.7 years). The phenotype of new onset IBD has changed significantly from historic cohorts (Table 1 ). There is a marked increase in the incidence of combined upper and lower gastrointestinal CD. Furthermore, there is a distinct increase in complex disease behaviour (27%) such as stricturing and penetrating disease. The incidence of UC (n=29) has increased three-fold in 10 years (16 boys, median age of diagnosis 13.1 years). Additionally, 59% of children were reported to have moderate to severe disease activity, similar to previously reported data. At one year, 21 (46%) children with CD and 19 (66%) children with UC children were in remission, with 91% of children steroid free. Conclusion: The incidence of IBD in Ireland remains high. The phenotypic behaviour of CD is changing with more complex disease behaviour evident at presentation. The prevalence of UC has tripled over 10 years. Future prospective longitudinal studies are needed to fully elucidate the factors underlying IBD in Irish children.